2017
DOI: 10.1093/ndt/gfx088
|View full text |Cite
|
Sign up to set email alerts
|

Renal safety of catheter-based renal denervation: systematic review and meta-analysis

Abstract: Based on meta-analyses of 52 studies and a qualitative review of an additional 14 studies, reporting on 2898 patients in total, we conclude that renal function does not significantly change up to at least 9 months after RDN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 41 publications
5
30
0
Order By: Relevance
“…We have also shown that patients who underwent RDN had no significant changes in renal function (eGFR) compared to the medical therapy group at 6 months post-renal denervation, supporting the safety profile of the procedure. Our findings are consistent with prior published studies 6,29 . The positive results noted in the newer trials did not affect the overall result of the meta-analysis.…”
Section: Discussionsupporting
confidence: 94%
“…We have also shown that patients who underwent RDN had no significant changes in renal function (eGFR) compared to the medical therapy group at 6 months post-renal denervation, supporting the safety profile of the procedure. Our findings are consistent with prior published studies 6,29 . The positive results noted in the newer trials did not affect the overall result of the meta-analysis.…”
Section: Discussionsupporting
confidence: 94%
“…Previously published studies in humans have concluded that RDN is generally safe in terms of kidney structure and function assessed as eGFR, both in the short and long term 12,16,19,32 . However, our study on patients with TRHT and relatively well‐preserved kidney function at baseline suggests that a clinically significant GFR decline may occur.…”
Section: Discussionmentioning
confidence: 53%
“…Multiple clinical trials are underway to test the effect of catheter‐based renal denervation in obese, drug‐resistant cases of hypertension (Mahfoud et al, 2011). These cohorts suggested that renal denervation is safe (Kandzari et al, 2018; Sanders et al, 2017). The primary safety end point was most often a composite of death, end‐stage renal disease, embolic events resulting in end‐organ damage, and renovascular complications.…”
Section: Discussionmentioning
confidence: 99%